2011
DOI: 10.1124/dmd.110.037374
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Distribution, Metabolism, and Excretion of [14C]GDC-0449 (Vismodegib), an Orally Active Hedgehog Pathway Inhibitor, in Rats and Dogs: A Unique Metabolic Pathway via Pyridine Ring Opening

Abstract: ABSTRACT:2-Chloro-N-(4-chloro-3-(pyridin-2-yl)-phenyl)-4-(methylsulfonyl)-benzamide (GDC-0449, vismodegib) is a potent and selective first-inclass small-molecule inhibitor of the Hedgehog signaling pathway and is currently in clinical development. In this study, we investigated the metabolic fate and disposition of GDC-0449 in rats and dogs after a single oral administration of [ 14 C]GDC-0449. An average of 92.4 and 80.4% of the total administered radioactivity was recovered from urine and feces in rats and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…In previous in vivo studies, vismodegib was shown to form three pyridine ring-opened metabolites M9, M13, and M18 (Graham et al, Yue et al, 2011). These metabolites were excreted mainly in feces, with the greatest amount in the dog (15%), followed by similar amounts in the excreta of human and rat (;5%).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous in vivo studies, vismodegib was shown to form three pyridine ring-opened metabolites M9, M13, and M18 (Graham et al, Yue et al, 2011). These metabolites were excreted mainly in feces, with the greatest amount in the dog (15%), followed by similar amounts in the excreta of human and rat (;5%).…”
Section: Discussionmentioning
confidence: 99%
“…An aliquot of a rat bile sample was extracted with ethyl acetate, and the organic phase was removed and dried as previously reported (Yue et al, 2011). The sample was reconstituted in 18 O-water with or without sulfuric acid (0.5 N).…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 3 more Smart Citations